2014
DOI: 10.5012/bkcs.2014.35.12.3489
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dithiolopyrrolone Derivatives and Their Leukocyte-Increasing Activities

Abstract: In search of new antileukopenia agents, twenty dithiolopyrrolone derivatives were synthesized and evaluated for their leukocyte-increasing activities in normal mice. Among the synthesized compounds 4-23, compounds 5 and 6 showed significant leukocyte-increasing activity ( p < 0.01), and compounds 4, 9 and 16 had a moderate effect ( p < 0.05). Compound 5 also displayed stronger leukocyte-increasing activity than that of the positive recombinant human granulocyte colony stimulating factor (rhG-CSF). Above all, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The synthesis procedures for N ‐aryl pyrrothine derivatives are shown in Scheme 1, following the synthesis routes on previous reports with minor modifications (Li, Wever, et al, 2014; Li, Sun, et al, 2014; Tan et al., 2013). The starting material of compound 1 was obtained according to previous procedure (Tan et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The synthesis procedures for N ‐aryl pyrrothine derivatives are shown in Scheme 1, following the synthesis routes on previous reports with minor modifications (Li, Wever, et al, 2014; Li, Sun, et al, 2014; Tan et al., 2013). The starting material of compound 1 was obtained according to previous procedure (Tan et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Dithiolopyrrolones are a class of antibiotics that possess the unique pyrrolinonodithiole (4 H ‐ [1,2] dithiolo [4,3‐ b ] pyrrol‐5‐one) skeleton (Qin, Huang, Yu, & Deng, 2013). Currently, there are approximately 30 naturally occurring dithiolopyrrolone derivatives identified, including thiolutin, holomycin, aureothricin, xenorhabdin I, and thiomarinols (Figure 1) (Gao et al., 2014; Li, Wever, Walsh, & Bower, 2014; Li, Sun, Wang, & Tan, 2014; Maffioli et al., 2017). These derivatives belong to N ‐methyl, N ‐acyl pyrrothine (thiolutin type), N ‐acyl pyrrothine (holomycin type), and thiomarinols.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[194][195][196][197][198][199] N-Aryl DTP analogues have been shown antitumor activity 198 and antileukopenia activity. 194,197 N-Aryl DTP with 2,4-dimethoxyphenyl moiety displayed potent antibacterial activity against clinical isolates of MRSA, RRSA, vancomycin-resistant S. aureus (VRSA), and moderately penicillin-resistant S. pneumoniae (MPRSP) with MIC values in the range of 0.125-2 mg mL À1 comparable to the antibiotic rifampin. 195 Previous works also showed that the biosynthetic pathway of DTPs is susceptible to be manipulated by feeding different organic acids or fatty acids to the cultures to modify the lateral acyl chain.…”
Section: Nat Prod Repmentioning
confidence: 99%